A Method of Demarcating Critical Failure Impedance Boundary of Multi-Infeed HVDC Systems Based on Minimum Extinction Angle. (1st September 2021) - Zhang, Song; Li, Guoqing; Li, Shuguang; Liu, Xintong
Abstract : A method of rapidly demarcating the critical commutation failure (CF) region of a multi-infeed high-voltage direct-current (HVDC) system is proposed. Based on the nodal impedance matrix and nodal voltage interaction factor, for different AC fault conditions—both balanced and unbalanced—a method of calculating the extinction angles of converters in multi-infeed HVDC systems is deduced in detail. First, the extinction angles of convertor stations under single-phase, double-phase, and three-phase ground faults and line-to-line faults occurring at any bus in an AC system are calculated. The minimum extinction angle serves as a CF criterion. If the calculated extinction angle for a certain bus is smaller than the minimum extinction angle, then a fault at that bus will cause CF of the HVDC system and put that bus into a failed bus set. The critical failure impedance boundaries of the topology diagram can therefore be demarcated by examining every bus in the AC system. The validity and accuracy of the proposed index and the method were verified by calculation results based on the three-infeed HVDC system model of the IEEE 39-bus system. Finally, the critical failure impedance boundary was demarcated in the IEEE 118-bus system to demonstrate the application in a wider range of systems.